2000
DOI: 10.1021/ja001871b
|View full text |Cite
|
Sign up to set email alerts
|

Chain-Growth Polycondensation for Nonbiological Polyamides of Defined Architecture

Abstract: Many natural polymeric materials are perfect monodisperse macromolecules and are produced by the successive condensation of monomers with polymer end groups that are activated by enzymes. [1][2][3][4] Although these syntheses proceed via many complicated and tightly controlled processes, the overall process could be regarded as a kind of chain-growth polycondensation. In the polycondensation of artificial monomers, however, macromolecules with a wide range of molecular weights have been synthesized, because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 15 publications
2
110
0
Order By: Relevance
“…Consequently, MI-1 served as an initiator for the polymerization of 1 despite the steric hindrance of the polystyrene backbone, and the block copolymer of polystyrene and poly1 was synthesized in a controlled fashion. Then, N-octyl-N-triethylsilylaniline (3), 4 which generates a stronger base than triethylsilane in the presence of fluoride ions, was used instead of triethylsilane to yield the block copolymer (entry 5), whose GPC elution curve was unimodal without shoulders [ Fig. 1(d)].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, MI-1 served as an initiator for the polymerization of 1 despite the steric hindrance of the polystyrene backbone, and the block copolymer of polystyrene and poly1 was synthesized in a controlled fashion. Then, N-octyl-N-triethylsilylaniline (3), 4 which generates a stronger base than triethylsilane in the presence of fluoride ions, was used instead of triethylsilane to yield the block copolymer (entry 5), whose GPC elution curve was unimodal without shoulders [ Fig. 1(d)].…”
Section: Resultsmentioning
confidence: 99%
“…4 This polymerization shows the feature of living polymerization. Thus, we have demonstrated that a sequential monomer addition method gives block copolyamides having different aminoalkyl side chains.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…18-Crown-6 (TCI) was used after drying overnight under reduced pressure at 50 C. N-Octyl-N-triethylsilylaniline (2) was prepared as described previously. 6 …”
Section: Experimental Materialsmentioning
confidence: 99%